Riskbedömningens logiker i arbetet med mäns våld mot kvinnor - Skillmark, Mikael (Socialvetenskaplig tidskrift, 2018)
Risk assessment logics when working with men’s violence against women Over the past two decades, social workers’ assessment and decision-making skills in client cases have been the subject of increased attention. The profession’s ability to conduct accurate assessments has been questioned. One way to seek to improve assessment work has been to implement various risk assessment tools. This article describes how social workers reason in risk assessment situations involving women exposed to violence by a previous male partner. The assessments studied here have been carried out with the assessment tool FREDA. The analysis reveals three logics in the social workers’ reasoning: the addiction logic, the normalization logic and the safety logic. These logics illustrate how social workers’ deliberations and assessments are not governed in a rectilinear manner by the standardized tool but that risk is negotiated also by drawing on other knowledge sources. Although standardization can be seen as a way for professionals to strive for more secure social work, the participants at the same time acknowledge the uncertainty associated with assessment work in which future violence is to be predicted. This however can have consequences for how the victims of violence are expected to live their lives.